Economic Assessment of Sanitation Interventions in Yunnan Province, People's Republic of China - World Bank (Washington, DC, 2014)
This study evaluates the costs and benefits of technical sanitation options and programs in Yunnan Province, China, as part of the Economics of Sanitation Initiative (ESI) conducted by the World Bank's Water and Sanitation Program in East Asia. As an underdeveloped province, Yunnan has achieved huge progress in sanitation improvement since the 1990s. Sanitation options evaluated in the study include the facilities to collect and convey human excreta, household wastewater treatment, and related hygiene practices. The benefits of sanitation evaluated include health, water quality, time to access sanitation facilities, external environment, reuse of human excreta, quality of life improvement, and other intangible benefits such as privacy, cleanliness and comfort. The costs of sanitation measured include investment costs and recurrent costs (operations and maintenance). The study compares the costs and benefits of alternative improved sanitation options over the expected life of each technology, to estimate efficiency of alternative sanitation options. For the study sanitation options in eight different sites throughout Yunnan Province were selected. Three rural sites include: a) villages in Luquan county s mountainous rural villages (R1); b) Dali Shangguan (R2) lakeside plain; and c) villages in Qiubei county (R3). Three urban sites represent: a) Kunming (U1); b) Dali (U2); and c) Qiubei (U3). Two peri-urban sites include: a) Kunyang town of Jinning County (PU1) and b) Dali Zhoucheng (PU2). The economic returns on all improved sanitation options are significant in all the sites evaluated, when compared with no access to basic sanitation.